Structure Analysis of Marine Pipes under the Effect of Water Explosion Force (Wave) - Kamran Khalifehei (Salehan Institute of Higher Education, 2017)
Underwater explosion is a subject that has been paid attention to by many researchers. In this study the underwater explosion phenomena under shockwave loading is explored by numerical method. For this purpose, by modeling a marine pipe buried in the water by ABAQUS software, the effect of the shock wave and the damages were assessed. Then using the laboratorial results, the fluid-structure interaction and shock wave loading and its results were analysed. Finally, it was concluded from numerical modeling that the highest levels of strain on the pipe buried in the water under underwater explosion and shock wave loading occur in the ending parts of the pipe in both sides and away from explosion field.